2021
DOI: 10.3390/biom11020193
|View full text |Cite
|
Sign up to set email alerts
|

Triaging of Culture Conditions for Enhanced Secondary Metabolite Diversity from Different Bacteria

Abstract: Over the past decade, the one strain many compounds (OSMAC) approach has been established for the activation of biosynthetic gene clusters (BGCs), which mainly encode the enzymes of secondary metabolite (SM) biosynthesis pathways. These BGCs were successfully activated by altering various culture conditions, such as aeration rate, temperature, and nutrient composition. Here, we determined the biosynthetic potential of 43 bacteria using the genome mining tool antiSMASH. Based on the number of BGCs, biological s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 70 publications
(34 reference statements)
0
15
0
Order By: Relevance
“…As a fact, through culture media variation (i.e., varying the concentration of carbon, nitrogen, phosphorous, inorganic salts, etc. ), it is possible to upregulate or trigger the production of certain secondary metabolites produced by talented microorganisms [7,[46][47][48]. In this study, the OSMAC strategy associated to bioassays allowed the selection of a specific growth condition expressing unique, structurally related metabolites, as highlighted by molecular networking (MN).…”
Section: Discussionmentioning
confidence: 99%
“…As a fact, through culture media variation (i.e., varying the concentration of carbon, nitrogen, phosphorous, inorganic salts, etc. ), it is possible to upregulate or trigger the production of certain secondary metabolites produced by talented microorganisms [7,[46][47][48]. In this study, the OSMAC strategy associated to bioassays allowed the selection of a specific growth condition expressing unique, structurally related metabolites, as highlighted by molecular networking (MN).…”
Section: Discussionmentioning
confidence: 99%
“…Acquisition by the DAD detector was performed at 400 nm and by the mass spectrometer, in positive mode from 90 to 900 m/z. The source parameters were established similar to previous publications [ 53 , 54 , 55 ]: 4 bar for nebulizing gas pressure, 12 L/min for a dry gas (N2) flow, 220 °C for the desolvation gas (N2) temperature, and 4.5 kV for a capillary voltage.…”
Section: Methodsmentioning
confidence: 99%
“…Although a high number of BGCs can be found in the genome of C. coralloides (Figure S1), none of the predicted compounds were detected up to now [11]. Thus, the activation of the biosynthetic potential requires a different approach.…”
Section: Resultsmentioning
confidence: 99%
“…coralloides possesses a large genome of 10.08 Mbp and 33 BGCs coding for potential SMs and accordingly has a large biosynthetic potential [11] (and new genome analysis for this study). However, in our previous study, we found that C. coralloides produced only 35 new MFs in response to various OSMAC stimuli [11]. Previous experience suggests that the number of new MFs should be much higher in terms of genome size and the number of BGCs predicted.…”
Section: Discovery Of New Secondary Metabolite Mfs After Bivariate Os...mentioning
confidence: 99%
See 1 more Smart Citation